Influence of amang (Tin Tailing) on geotechnical properties of clay soil (Pengaruh amang timah terhadap sifat geoteknik tanih lempung) - Zulfahmi Ali Rahman,; Wan Zuhairi, W. Y; Raihan, M.T; Sahibin, A. R.; Wan Mohd Razi, I; Tukimat, L; Siti Nur Syakireen, Z; Noorulakma, A (Universiti Kebangsaan Malaysia, 2012)
Amang or tin tailing is commonly found in the vicinity of disused mining area and responsible in downgrading the water quality, landscape and mechanical behaviour of soils. It was generated from extraction process of separating valuable metal from particular ore. This paper presents the geotechnical characteristics of amang-contaminated clay soil. The geotechnical properties of uncontaminated soils were studied in order to compare to that of amangcontaminated soils. The base soil used in this study represents completely weathered horizon of metasedimentary rock. Meanwhile, tin tailing sample was taken from the disused mine at Sungai Lembing, Pahang. The geotechnical characterisations of base soil and contaminated soils were determined based on consistency index, compaction behaviour, hydraulic conductivity and undrained shear strength (UU tests). Contaminated soil samples were prepared by adding 5, 10 and 20% of tailing, based on dry weigh of the studied base soil. The results from the particle size distribution analysis showed that residual soil from metasedimentary rock comprised 42.6% clay, 32.2% silt and 25.2% sand whilst tailing was dominated by 98% of sand fraction. XRD analysis indicated the presence of quartz, kaolinite and muscovite minerals in the studied soil. The specific gravity of soil used is 2.67 and the pH is 3.88. Tailing found to have higher specific gravity of 3.37. The consistency index of contaminated soils showed that liquid limit, wL and plastic limit, wP decreased with the increase in the percentage of tailing added to the soil samples. The value of maximum dry density, ρ dry max increased while optimum moisture content decreased due to the increase in tailing content in soil sample. The permeability of contaminated soil also increased with the increase in tailing contents ranged from 19.8 cm/hr to 23.8 cm/hr. The undrained shear strength, Cu, of contaminated soil decreased from 646 kPa (5% of tailing) to 312 kPa (20% of tailing) suggesting that the presence of tailing has influenced the geotechnical properties on the studied soil.